[Viterbo Collection] - Medori, Angelo 1839-1894
Despite his modest origins, Angelo Medori's talent induced his father to enroll him at the Liceo musica di Bologna where he graduated with honors in composition in 1866. The same year he returned to Viterbo where he was elected choirmaster of the cathedral. She also held the position of director of the municipal band for sixteen years and that of teacher in the municipal music school. In 1878 he became an honorary member of the Academy of Santa Cecilia. He composed numerous pieces of music and in 1887 he ventured into melodrama with the four-act opera 'La Galiana', legendary heroine from Viterbo, represented at the Teatro Unione on 8 September 1887.
Collection of scores of 11 works by various composers, mostly manuscript.
Selection digitized by iGuana, Spring 2022
Purchased by Ton Koopman in Viterbo, Italy